Both-side approximation of solutions of differential equations - Kopach, M.I.; Obshta, A.F.; Shuvar, B.A. (Carpathian Mathematical Publications, 2009)
Both-side algorithms analogs of the Chaplygin method for ordinary differential equations. Conditions of algorithms squared convergence even in the case of operator nondifferentiability have been established.